Structure‐from‐motion photogrammetry demonstrates that fine‐scale seascape heterogeneity is essential in shaping mesophotic fish assemblages. Issue 6 (19th July 2022) - Swanborn, Denise J. B.; Stefanoudis, Paris V.; Huvenne, Veerle A. I.; Pittman, Simon J.; Woodall, Lucy C.
Abstract: Benthic components of tropical mesophotic coral ecosystems (MCEs) are home to diverse fish assemblages, but the effect of multiscale spatial benthic characteristics on MCE fish is not well understood. To investigate the influence of fine‐scale benthic seascape structure and broad‐scale environmental characteristics on MCE fish, we surveyed fish assemblages in Seychelles at 30, 60 and 120 m depth using submersible video transects. Spatial pattern metrics from seascape ecology were applied to quantify fine‐scale benthic seascape composition, configuration and terrain morphology from structure‐from‐motion photogrammetry and multibeam echosounder bathymetry and to explore seascape–fish associations. Hierarchical clustering using fish abundance and biomass data identified four distinct assemblages separated by the depth and geographic location, but also significantly influenced by variations in fine‐scale seascape structure. Results further revealed variable responses of assemblage characteristics (fish biomass, abundance, trophic group richness, Shannon diversity) to seascape heterogeneity at different depths. Sites with steep slopes and high terrain complexity hosted higher fish abundance and biomass, with shallower fish assemblages (30–60 m) positively associated with aggregated patch mixtures of coral, rubble, sediment and macroalgae with variable patch shapes. Deeper fish assemblages (120 m) were positively associated with relief and structural complexity and local variability in the substratum and benthic cover. Our study demonstrates the potential of spatial pattern metrics quantifying benthic composition, configuration and terrain structure to delineate mesophotic fish–habitat associations. Furthermore, incorporating a finer‐scale perspective proved valuable to explain the compositional patterns of MCE fish assemblages. As developments in marine surveying and monitoring of MCEs continue, we suggest that future studies incorporating spatial pattern metrics with multiscale remotely sensed data can provide insights will that are both ecologically meaningful to fish and operationally relevant to conservation strategies. Abstract : To investigate the influence of benthic seascape structure on MCE fish assemblages in Seychelles, this study surveyed benthic structure and fish assemblages using submersible video transects at mesophotic depths. Spatial pattern metrics measuring benthic habitat composition, configuration and terrain structure were extracted from Structure‐from‐Motion photogrammetry models to quantify fish‐habitat associations. The results revealed depth‐ and site driven grouping of mesophotic fish assemblages that show significant associations with fine‐scale (cm‐m) terrain structure, seascape composition and configuration.